2006
DOI: 10.1191/0265659006ct303oa
|View full text |Cite
|
Sign up to set email alerts
|

Working with pre-school practitioners to improve interactions

Abstract: Eight pre-schools tookpart in offsite and onsite speech and language training to improve their interaction skills with children and learn some group language activities. An evaluation was undertaken where practitioners at one pre-school were videoed running a language activity before and after training. The video was analysed to assess change in adult and child interaction. All practitioners who had undertaken the training were interviewed to find out about its impact in their setting. The research showed stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The results by Girolametto et al (2003) show the significant effects of the program ''Learning Language and Loving It-The Hanen Program for Early Childhood Educators'' on the LSP of educators. Other programs targeting educators also report significant improvements in children's language skills, such as the Language-Focused Curriculum (Justice et al 2008b) and the Speech and Language Training for Preschool Practitioners (Ahsam et al 2006). Those results underscore the importance of integrating specific language training into ECE training.…”
Section: Itemsmentioning
confidence: 88%
See 1 more Smart Citation
“…The results by Girolametto et al (2003) show the significant effects of the program ''Learning Language and Loving It-The Hanen Program for Early Childhood Educators'' on the LSP of educators. Other programs targeting educators also report significant improvements in children's language skills, such as the Language-Focused Curriculum (Justice et al 2008b) and the Speech and Language Training for Preschool Practitioners (Ahsam et al 2006). Those results underscore the importance of integrating specific language training into ECE training.…”
Section: Itemsmentioning
confidence: 88%
“…Girolametto et al (2003) make the distinction that educators with specialized language training are more likely to use responsiveness in their interactions with children-such as listening and responding to initiatives-than educators without such training, who tend to use more directiveness in their interactions with children. Caregiver responsiveness is associated with better language skills in children (Ahsam et al 2006;Girolametto et al 2003;Tennant et al 1988). By following the children's lead, educators can build on their interests and capture their attention, which encourages children to enjoy the process and to want to communicate more.…”
Section: Promoting Language Skills In Childrenmentioning
confidence: 99%
“…One study (Ahsam et al, 2006) had to be excluded because it did not give enough information to enable us to calculate an effect size, even though the study satisfied all other inclusion criteria. This study reported a significant effect of a training program on children's interaction and communication skills.…”
Section: E X T R Ac T I N G An D C Al C U L At I N G E F F E C T S Imentioning
confidence: 99%
“…Training in child language development is clearly necessary in order to meet the educational needs of ECEs (Lanigan, 2011). Ahsam et al (2006) developed a 12-week onsite training package for ECEs, whereby a speech-language pathologist (SLP) or SLP assistant attended the childhood setting for one session per week. The ECE initially observed the SLP modelling language activities in small groups then ran the activity, and received feedback from the SLP.…”
Section: Introductionmentioning
confidence: 99%